2001
DOI: 10.1073/pnas.98.4.1665
|View full text |Cite
|
Sign up to set email alerts
|

Lamprey Dlx genes and early vertebrate evolution

Abstract: Gnathostome vertebrates have multiple members of the Dlx family of transcription factors that are expressed during the development of several tissues considered to be vertebrate synapomorphies, including the forebrain, cranial neural crest, placodes, and pharyngeal arches. The Dlx gene family thus presents an ideal system in which to examine the relationship between gene duplication and morphological innovation during vertebrate evolution. Toward this end, we have cloned Dlx genes from the lamprey Petromyzon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 59 publications
8
120
1
Order By: Relevance
“…Our findings might imply, more generally, that Dlx genes were needed to allow asymmetry when required by the rise of complex anatomical structures during evolution. Our data reinforce the concept, already present in the literature that Dlx genes are associated with the appearance of morphological novelties in vertebrates (Neidert et al, 2001).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings might imply, more generally, that Dlx genes were needed to allow asymmetry when required by the rise of complex anatomical structures during evolution. Our data reinforce the concept, already present in the literature that Dlx genes are associated with the appearance of morphological novelties in vertebrates (Neidert et al, 2001).…”
Section: Resultssupporting
confidence: 92%
“…Based on sequencing comparison, it is thought that during the evolution of chordates an initial gene duplication occurred, followed by several cluster duplications and selective gene losses (Stock et al, 1996;Ruddle, 1997;Zerucha and Ekker, 2000). Dll homologs have been isolated from vertebrate species like lamprey, zebrafish, newt, Xenopus, mouse, and human (see Neidert et al, 2001, and references therein). They constitute a highly conserved family of homeobox genes, which are thought to act as transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these differences suggest that the dorsal and ventral elements of the branchial basket may consist of two separate embryonic components. In jawed vertebrates, the nested expression of dlx genes is important for establishing dorsoventral (proximodistal) polarity in branchial arches (Panganiban and Rubenstein, 2002;Depew et al, 2005), although Langeland and his colleagues (Neidert et al, 2001) reported no dorsoventral patterning of dlx expression in is attached to the parachordal cartilage lateral to the notochord. Remaining caudal skeletal rods (PA4-9) attach to the subchordal cartilages on the ventral surface of the notochord.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…In vertebrates, all Dlx genes except zebrafish dlx2b, are expressed in ectomesenchymal cells derived from the cranial neural crest (DollĂ© et al, 1992;Bulfone et al, 1993;Akimenko et al, 1994;Robinson and Mahon, 1994;Simeone et al, 1994;Qiu et al, 1997;Yang et al, 1998;Davideau et al, 1999;Myojin et al, 2001;Neidert et al, 2001). The migratory neural crest cells populate the branchial arches, which in turn give rise to much of the craniofacial skeleton and connective tissue (Depew et al, 2002).…”
Section: In the Zebrafish DLX Genes Are Expressed In The Visceral Skmentioning
confidence: 99%
“…To account for the present complement of six mammalian Dlx genes, i.e., Dlx1, Dlx2, Dlx3, Dlx4 (formerly Dlx7), Dlx5, Dlx6, a tandem duplication of an ancestral Dlx gene has been proposed to have been followed by two rounds of genome duplication and a subsequent loss of one Dlx pair (Ellies et al, 1997;Neidert et al, 2001).…”
Section: Introductionmentioning
confidence: 99%